NaV1.5 or KCa2 channel blockade does not increase arrhythmia risk in hypokalemic rabbit hearts, unlike KV11.1 inhibition with dofetilide - Yannan Yan; Lea Abildgaard; Mark Alexander Skarsfeldt; Sofia Hammami Bomholtz; Ulrik Sørensen; Anders Gaarsdal Holst; Morten Grunnet; Jonas Goldin Diness; Bo Hjorth Bentzen (International Journal of Cardiology: Heart & Vasculature)
Aims: The small conductance calcium activated potassium channel (KCNN1-3; KCa2.1–3) is recognized as a possible new anti-arrhythmic drug target for treatment of atrial fibrillation (AF). The aim of this study is to investigate potential ventricular effects of KCa2 channel inhibition under normal, bradycardic and hypokalemic conditions and compare these to classical class I and III anti-arrhythmic drugs. Methods and results: Rabbit hearts were isolated, AV-ablated, mounted in an ex vivo Langendorff preparation and perfused with normokalemic (4 mM K+) Krebs-Henseleit solution, followed by perfusion with drug (AP14145 3 µM; AP30663 1.5 µM; dofetilide 10 nM; flecainide 1.5 µM) or vehicle control. The perfusion was then changed to hypokalemic solution (2.5 mM K+) in presence of drug. Changes in ventricular action potential duration were assessed by monophasic action potential recordings. Neither of the KCa2 channel inhibitors (AP14145 or AP30663) or flecainide (NaV1.5 inhibitor) prolonged ventricular action potential duration (APD90) or increased pro-arrhythmic markers, whereas dofetilide (KV11.1 blocker) prolonged APD and increased the susceptibility to ventricular arrhythmia. Conclusions: These findings suggests that KCa2 channels have minimal importance for ventricular repolarization in healthy rabbit hearts under both normo- and hypokalemic conditions.